Study of flow over dimpled cylinder - Lim, Meng Hee. (2013)
Fluid flow around a circular cylinder is controlled by dimpling the surface of the cylinder to reduce drag forces acting on it. Numerical simulation and wind tunnel experimentation on the flow around a smooth and dimpled cylinder are carried out to investigate the effectiveness of dimples on drag reduction.